Masculinidades plurais, ativismo de marcas e ativismos de consumidores-fãs-fiscais - Postinguel, Danilo (2019)
This thesis had as object of study audiovisual representations of advertising masculinities. We take into consideration for analysis, the processes of communication and consumption mobilized, or in which these representations arise, the visibility regimes articulated by them and the sociocultural reception contexts in which they are inserted. Our main objective was to understand advertising representations of masculinities, understood as man/male drives that escape or impact conventional or hegemonic patterns, both culturally and aesthetically, as well as regarding heteronormativity. From these contexts, our secondary objectives were: a) to analyze social changes regarding masculinities debates and man crossed by mediatization processes; b) identify new visibility regimes in the advertising field, associated with these ambivalent or dissonant media representations; c) problematize the relations established between these two planes, from a non-deterministic point of view or from strict causality; d) reflect on a politicization of/for consumption by advertisers and brands around the gender debate about masculinities; and e) problematize new media consumption practices articulated with perspectives of engaged reception. As for the theoretical contribution, Mônica Machado, Raewyn Connell, Rogério Covaleski, Rose de Melo Rocha, Tânia Hoff among other theorists who contributed to theorize masculinities and politicization through advertising consumption. In methodological terms, we opted for a “social listening”, observing, selecting and analyzing the conversation of subject-consumers around the unfolding of the selected corpus in digital environments. We selected for the corpus advertisements coming from brands of the cosmetic segment, from an interested investigation of commercials, locating the acceptance or the denial of these advertising campaigns and their developments in social media. Among the results, we highlight the “pollination effect” of the analyzed publicities, imagetic, symbolic and sensitive. We also realize that such advertisements reveal brand activism that implies social processes of rethinking masculinities. Still composing the process of this media consumption, we identified the formation of subject-consumers who, while they may be fans of brands, are more aware to their discourses, constituting the dimensions of consumer-fanvigilant and consumer activist.